2003
DOI: 10.1523/jneurosci.23-14-05975.2003
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2Activates the Histaminergic System via the EP4Receptor to Induce Wakefulness in Rats

Abstract: Prostaglandin (PG)E2 promotes the wakeful state when administered into the posterior hypothalamus, in which the histaminergic tuberomammillary nucleus (TMN) is located. To explore the neurotransmitter mechanisms responsible for PGE2-induced wakefulness in rats, we examined the effect of PGE2 on the activity of the histaminergic system and the involvement of PGE2 receptor subtypes in the response. PGE2 perfusion in the TMN at doses of 100, 200, and 400 pmol/min for 2 hr significantly increased histamine release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…Bicuculline (5 mg/kg, i.p.) and flumazenil, antagonists for the binding site of GABA and benzodiazepine, respectively, of the GABA A receptor, also inhibited the anxiolytic-like activity induced by the central administration of PGE 2 (Fig. 6).…”
Section: Activation Of Ep 1 /Ep 4 Receptors Exhibits Anxiolytic-like mentioning
confidence: 86%
See 3 more Smart Citations
“…Bicuculline (5 mg/kg, i.p.) and flumazenil, antagonists for the binding site of GABA and benzodiazepine, respectively, of the GABA A receptor, also inhibited the anxiolytic-like activity induced by the central administration of PGE 2 (Fig. 6).…”
Section: Activation Of Ep 1 /Ep 4 Receptors Exhibits Anxiolytic-like mentioning
confidence: 86%
“…Although the EP selective drugs used in this study have been shown to be selective across EP receptor subtypes, we sought to confirm the involvement of EP 1 /EP 4 receptors in the anxiolytic-like activity by using knockout mice deficient in each EP subtype [9,14]. Genetic deletion of the EP 4 receptor abolished the anxiolytic-like activity of PGE 2 (Fig. 5A).…”
Section: Activation Of Ep 1 /Ep 4 Receptors Exhibits Anxiolytic-like mentioning
confidence: 98%
See 2 more Smart Citations
“…mPGES-1 is induced in the delayed phase of inflammation, with activation time occurring in the course of approximately 1 hour. It is involved in wakefulness, inflammation, hyperalgesia, pain, fever, and cancer [16,19]. Its expression, together with that of COX-2, is induced by proinflammatory stimuli such as IL-1β and has been suggested to be down-regulated by antiinflammatory glucocorticoids, docosahexaenoic acid, and eicosapentaenoic acid [16,20].…”
Section: Introductionmentioning
confidence: 99%